Meta-Analisis Pengaruh Penggunaan Media Pembelajaran Video Terhadap Hasil Belajar Siswa Pada Pembelajaran Imu Pengetahuan Alam - adha, intan aulia (Universitas Negeri Padang, 2020)
Media video learning is one of the means used to facilitate the learning process at school. Video learning media is an audio-visual type of learning media equipped with moving images, text, and sound so that students are more interested in learning during the learning process and can affect student learning outcomes. This study aims to analyze the effect of video learning media on student learning outcomes. This research method is a meta-analysis method with a sample of 10 articles in national and international journals. The instrument used was a sheet presenting the code (coding category). Based on the results of the meta-analysis research, it shows that the use of video learning media has an influence on student learning outcomes. The effect size value is 1.43 which indicates the high category, which means that effective video learning media are used during the learning process so that it can affect student learning outcomes. <w:LsdException Locked=